2017
DOI: 10.3384/ecp17138157
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of burning velocities in gases vented from thermal run-a-way lithium ion batteries

Abstract: This paper describes the results from simulations of laminar burning velocities in the premixed air and flammable gases vented from abused Li-ion batteries. The released mixture from such batteries contain mixtures of hydrogen, methane, ethylene, carbon monoxide and carbon dioxide. The study also includes the combustion properties of an electrolyte, dimethyl carbonate. The simulation results show the laminar burning velocities as a function of concentration, pressure and temperature for the gas mixtures and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Accurate quantification of ejection velocity and temperature of these materials are a challenging subject. So far, most studies aimed to analyze the combustion chemistry of the organic solvents used in LIB [149] or the mixture of the vented gases at TR [150,151].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate quantification of ejection velocity and temperature of these materials are a challenging subject. So far, most studies aimed to analyze the combustion chemistry of the organic solvents used in LIB [149] or the mixture of the vented gases at TR [150,151].…”
mentioning
confidence: 99%
“…Johnsplass et al [151] modelled the laminar burning velocities of the ejecting gases from the LIB premixed with air. It was reported that the burning of vented gases is comparable to propane and methane, presenting a serious hazard of explosion and fires in enclosures, and laminar burning velocities of the gases are similar or slightly higher than that of methane.…”
mentioning
confidence: 99%
“…Due to the challenges in accurate measurement of venting gas composition, ejection flow, and combustion reaction mechanisms, a comprehensive simulation of fires produced by flammable gases and other battery materials venting from a battery cell has not been conducted [113]. Most of the existing studies [114][115][116][117][118] aimed to analyze the explosion characteristics or combustion properties of the vented gases and estimate their flammability risk and combustion intensity. The explosion characteristics include (but not limited to) combustion energy [114], laminar burning velocity [115,118], explosion pressure [116][117][118], pressure rise rate [116,118], and laminar flame speed [117,118].…”
Section: Combustion Modelsmentioning
confidence: 99%
“…The combustion chemistry of the ejected materials has been addressed in some published studies to assess the thermal hazards [9,28,29]. Johnsplass et al [28] employed the Cantera 2.3.0 code with GRI-Mech 3.0 mechanism to simulate the combustion of three different kinds of abused LIBs in air. Fernandes et al [9] also investigated combustion properties of the released gases in the Chemical Workbench Code and CHEMKIN-II.…”
Section: Introductionmentioning
confidence: 99%